In Situ Quantification and Profiling of Phosphatidylcholine in Mouse Brain Tissue by Matrix‐assisted Laser Desorption Ionization with a Liquid Matrix. (18th May 2017) - Park, Kyung Man; Hyeon, Taeghwan; Kim, Myung Soo; Moon, Jeong Hee
Abstract : A method based on the analyte‐to‐matrix ion abundance ratio in the matrix‐assisted laser desorption ionization (MALDI) spectrum was used for the quantification of phosphatidylcholine (PC) in mouse brain tissue. The fact that the tissue was heavily contaminated and hence that the matrix suppression was unacceptably high forbade the in situ quantification of PC. We eliminated most of the polar contaminants, and some nonpolar ones as well, by washing the tissue with water. In the process, we observed the presence of two different populations of PC, one washable in water and the other unwashable. Finally, we present a quantitative profile of the unwashable PC in a mouse brain tissue evaluated from its MALDI spectral data. Abstract :